Juvenile Justice Contact, Educational Trajectories, and Recidivism: A Mixed Method Evaluation - Bond, Margaret (American journal of criminal justice, 2025)
Research demonstrates strong relationships between education and positive post-prison outcomes. Recognizing that educational trajectories can be disrupted early on, we investigate the impact of juvenile justice contact on educational attainment, educational aspirations, and recidivism. We examine relationships in data from two connected prison-based data collection projects both quantitatively (n = 174) and qualitatively (n = 88). We utilize Cox models to assess the impact of education on recidivism among a sample of incarcerated men with substance use disorders. Longitudinal in-depth semi-structured interviews reveal patterns of juvenile justice contact, perceptions of school, educational aspirations, and post-release outcomes. Quantitative analyses demonstrate that formal education attainment, but not intelligence, is significantly related to recidivism. The qualitative transcripts illustrate that juvenile justice contact can impede educational aspirations and achievement. We discuss policy implications, including making education, a consistent predictor of post-release success, accessible to incarcerated and reentering individuals and altering exclusionary school discipline policies.